Oscillatory and wave activity in the runaway electrons flow - Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Olshansky, V.V.; Lystopad, V.M.; Lymar, N.V.; Gnidenko, M.V. (Вопросы атомной науки и техники, 2016)
The presence of the accelerated particles flow (the flow of runaway electrons) in the plasma confinement volume may case a number of different instabilities. In this work we investigate the spectrum of fluctuations in a flow of charged particles to identify the oscillatory and wave processes observed. Besides, we pay special attention to the interaction between the flow particles and plasma fluctuations. The main evidence of such interaction is the presence of modulation in the particles flow with the corresponding characteristic modulation frequency. Namely, the modulation frequency in such cases corresponds to the frequency of characteristic oscillations of the discharge plasma. Basing on this, we carried out the experimental investigations of spectrum of oscillations observed in the circuits of edge electrostatic probes during the microwave pumping pulse and also on the back edge of the magnetic field pulse.